2007
DOI: 10.1007/s11187-007-9047-0
|View full text |Cite
|
Sign up to set email alerts
|

Firm Clustering and Specialization: A Study of Taiwan’s Machine Tool Industry

Abstract: Taiwan, machine tools, industrial districts, firm specialization, vertical integration, product scope, D20, L11, L22, L23, L26, O30, R30,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
3
12
0
Order By: Relevance
“…We can observe that agglomeration is negatively and significantly correlated with the degree of vertical integration, but only for the zip code. We also found a significant relationship between agglomeration and horizontal specialization, as Brookfield (2008) suggests.…”
Section: Variable Measurementssupporting
confidence: 80%
See 3 more Smart Citations
“…We can observe that agglomeration is negatively and significantly correlated with the degree of vertical integration, but only for the zip code. We also found a significant relationship between agglomeration and horizontal specialization, as Brookfield (2008) suggests.…”
Section: Variable Measurementssupporting
confidence: 80%
“…Storper and Christopherson (1987) described how the process of vertical disintegration that characterized the US motion-picture industry from the 1950s to the early 1980s led to significant changes in industrial location patterns, creating strong agglomeration tendencies. Later, Scott and Kwok (1988) and Brookfield (2008) tested and corroborated that vertical specialization was significantly associated with higher levels of spatial agglomeration in the printed-circuits industry of Southern California and the Taiwanese machine-tool industry, respectively. In a similar vein, Holmes (1999) confirmed that establishments that are located in areas where an industry was more concentrated were more likely to contract out than were those located in areas where industries were less concentrated, but he also found that this relationship varied across industries with different characteristics.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…They have highlighted the relationship between the geographic concentration of production and vertical integration (Cainelli and Iacobucci 2009;Holmes 1999;Helsley and Strange 2007;Brookfield 2008;Diez-Vial and Alvarez-Suescun 2010). They have highlighted the relationship between the geographic concentration of production and vertical integration (Cainelli and Iacobucci 2009;Holmes 1999;Helsley and Strange 2007;Brookfield 2008;Diez-Vial and Alvarez-Suescun 2010).…”
mentioning
confidence: 99%